2021
DOI: 10.1007/s11012-021-01329-z
|View full text |Cite
|
Sign up to set email alerts
|

Analogue tuning of particle focusing in elasto-inertial flow

Abstract: We report a unique tuneable analogue trend in particle focusing in the laminar and weak viscoelastic regime of elasto-inertial flows. We observe experimentally that particles in circular cross-section microchannels can be tuned to any focusing bandwidths that lie between the “Segre-Silberberg annulus” and the centre of a circular microcapillary. We use direct numerical simulations to investigate this phenomenon and to understand how minute amounts of elasticity affect the focussing of particles at increasing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…A possible explanation for this is the distorted first normal stress difference that builds up around the particle, leading to an oscillatory stretching around its surface. The interested reader is referred to the work by Indradumna 43 for further analysis of the different migration dynamics leading to the oscillatory behavior of particles in circular channels in weak fluid elastic flows. While more work is needed to fully elucidate the observation of weak oscillatory behavior, there is a huge potential to exploit the strict sizedependent migration of particles for high-resolution separation applications, which has been the focus of the current work.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A possible explanation for this is the distorted first normal stress difference that builds up around the particle, leading to an oscillatory stretching around its surface. The interested reader is referred to the work by Indradumna 43 for further analysis of the different migration dynamics leading to the oscillatory behavior of particles in circular channels in weak fluid elastic flows. While more work is needed to fully elucidate the observation of weak oscillatory behavior, there is a huge potential to exploit the strict sizedependent migration of particles for high-resolution separation applications, which has been the focus of the current work.…”
Section: Resultsmentioning
confidence: 99%
“…33 Furthermore, it was shown that the fibers can be co-drawn with compatible materials so that conductive domains can be integrated at arbitrary locations along channel walls. 43 In this work, we present elasto-inertial particle separation with high efficiency followed by particle counting in an integrated all-fiber microfluidic component. The overall configuration of the component is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation